First report on Rhabdocoela (Rhabditophora) from deep parts of Skagerrak, with the description of four new species. Zootaxa, 1616, 1–21. (ERRATUM) - Willems, W.; Sandberg, M. I.; Jondelius, U. (Zootaxa, 2007)
ERRATUM